2009
DOI: 10.4319/lo.2009.54.4.1272
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐decadal shoaling of the euphotic zone in the southern sector of the California Current System

Abstract: We document a long-term reduction in Secchi depth of 0.06-0.13 m yr 21 in the southern California Current System (CCS) over the period 1969-2007, reflecting a long-term shoaling of the euphotic zone. Calibrated water clarity observations from 1949 to 1954 reinforce the results indicating a progressive shoaling. For the inshore area, 150 km off the coast, Secchi disk has shoaled 8.4 6 1.2 m since 1949. This change has been accompanied by a nitracline shoaling of 18.2 6 6.4 m since 1969 and an increase in chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 27 publications
4
57
0
Order By: Relevance
“…The offshore nitracline depth is not only responsive to remote forcing on scales ranging from weekly (e.g., coastally trapped waves) to inter-annual (e.g., El Niñ o), but to inter-decadal scales as well (e.g., North Pacific Gyre Oscillation; di Lorenzo et al 2008). Aksnes and Ohman (2009) showed that, over the course of the last 25 yr, the depth of the nitracline has decreased and the integrated chlorophyll concentrations have increased throughout the SCB. Similarly, Kahru et al (2009), using satellite-derived estimates, have shown that primary productivity has increased as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The offshore nitracline depth is not only responsive to remote forcing on scales ranging from weekly (e.g., coastally trapped waves) to inter-annual (e.g., El Niñ o), but to inter-decadal scales as well (e.g., North Pacific Gyre Oscillation; di Lorenzo et al 2008). Aksnes and Ohman (2009) showed that, over the course of the last 25 yr, the depth of the nitracline has decreased and the integrated chlorophyll concentrations have increased throughout the SCB. Similarly, Kahru et al (2009), using satellite-derived estimates, have shown that primary productivity has increased as well.…”
Section: Discussionmentioning
confidence: 99%
“…Presently there is no convincing dynamical explanation for the observed biological changes, although variabilities in atmospheric and physical oceanographic processes are expected to be causative agents. For example, although increasing stratification was expected to suppress nitrate delivery to the euphotic zone of the SCB (Roemmich and McGowan 1995;di Lorenzo et al 2005), the opposite has apparently occurred, even in the absence of a strengthening in coastal wind-forced upwell-ing and only weak strengthening of wind stress curl over the SCB (Rykaczewski and Checkley 2008;Aksnes and Ohman 2009).…”
mentioning
confidence: 99%
“…The present study also provides a robust dataset to facilitate the development and testing of ecosystem models at the level of phytoplankton functional groups and to improve algorithms for extracting community biomass and composition information from satellite remote sensing measurements. Future climate changes in the southern CCE region are projected to include increased thermal stratification (Rykaczewski and Dunne, 2010), increased delivery of nitrate to coastal areas by upwelling (Bakun, 1990;Snyder et al, 2003;Aksnes and Ohman, 2009), and increased number and intensity of ocean frontal systems (Kahru et al, 2012), each capable individually of significantly impacting productivity, standing stocks and composition of the food web base, though their effects will likely differ spatially. Continued monitoring as well as experimental and modeling studies are needed to elucidate how such changes will combine to alter biogeochemical cycling and trophic coupling within the southern CCE region.…”
Section: Community Compositionmentioning
confidence: 99%
“…However, several authors have contested the methodology and implications of this study, some arguing that the long-term trend detected is an artifact of changes in the measurement techniques (Rykaczewski and Dunne, 2011;Mackas, 2011), and others reporting increases in chlorophyll a (hereafter chlorophyll) concentrations for regions that have been studied with consistent sampling methods over multi-decadal scales (e.g. Karl et al, 2001;Corno et al, 2007;Aksnes and Ohman, 2009; Published by Copernicus Publications on behalf of the European Geosciences Union. Lomas et al, 2010;Saba et al, 2010;McQuatters-Gollop et al, 2011).…”
Section: Introductionmentioning
confidence: 99%